Who is doing worse? Retrospective cross-sectional study of TB key population treatment outcomes in Kyrgyzstan (2015-2017) - Kozhoyarova, Aruuke; Sargsyan, Aelita; Goncharova, Olga; Kadyrov, Abdullaat (The Journal of Infection in Developing Countries, 2020)
Introduction: Tuberculosis (TB) is a global public health problem. The incidence of TB is especially high among TB key populations, such as the homeless, people who use drugs, prisoners, and migrants. The study aimed to assess the associations between affiliation to TB key populations and treatment outcome. Methodology: This retrospective cross-sectional study used data extracted from the National TB Registry of Kyrgyzstan for the region of Chuy (including the city of Bishkek) for 2015–2017. Descriptive statistics was used to summarize the data. Logistic regression was used to assess the associations. Results: The study included 1,526 patients among whom more than half (52.5%) fell into the youngest group (18-35 years old). Migrants were the most highly represented group comprising 67.8% of all TB key populations. Men (63.0%) and patients with pulmonary TB (83.0%) prevailed in the cohort. The proportions of patients who had completed the treatment were high among all the key populations. Logistic regression was used to assess the association between affiliation to a certain TB key population and the TB treatment outcome. Patients who belonged to more than one TB key population were found to have the highest risk of unsuccessful TB treatment outcomes, both in the region of Chuy (OR = 9.9, 95% CI 2.0–48.1, p = 0.04) and the city of Bishkek (OR = 24.9, 95% CI 7.2–86.4, p < 0.001). Conclusion: The homeless, people who use drugs, ex-prisoners, and TB patients who belonged to more than one TB key population were found to have higher risks of unsuccessful TB treatment outcome in comparison to migrants.